The banker`s new cloths: What wrong with banking and what to do about it - Admati, Anat; Hellwig, Martin (New Jersey Princeton University Press, 2013)
New bank failures have been a rude awakening for everyone who believed that the banking industry was reformed after the Global Financial Crisis$1 (Band that we$1 (Bd never again have to choose between massive bailouts and financial havoc. The Bankers$1 (BNew Clothes uncovers just how little things have changed$1 (Band why banks are still so dangerous. s